Grain Sorghum Tolerance and Weed Control with Pyrasulfotole plus Bromoxynil Combinations. Issue 1 (1st December 2013) - Fromme, Dan D.; Grichar, W. James; Dotray, Peter A.; Fernandez, Carlos J.
Abstract : Research was conducted in Texas from 2010 through 2012 to evaluate combinations of pyrasulfotole plus bromoxynil for weed control and grain sorghum [ Sorghum bicolor (L.) Moench] response. In most instances, combinations of pyrasulfotole plus bromoxynil applied early postemergence controlled Palmer amaranth ( Amaranthus palmeri S. Wats), devil's‐claw [ Proboscidea louisianica (Mill.) Thellung], pitted morningglory ( Ipomoea lacunosa L.), and smellmelon [ Cucumis melo L. subsp. agrestis (Naudin) Pangalo var. dudaim (L.) Naudin (syn. Cucumis melo L. var. dudaim Naud.)] at least 81%. However, these combinations controlled Texas millet [( Urochloa texana (Buckl.) L.] no more than 72%. Horse purslane ( Trianthema portulacastrum L.) was controlled completely when pyrasulfotole plus bromoxynil was applied to plants ≤10 cm in height but no more than 65% when applied to taller plants. Pyrasulfotole plus bromoxynil combinations injured grain sorghum transiently and injury was not apparent later in the season. Early season injury caused by combinations of pyrasulfotole plus bromoxynil did not adversely affect yield except in the case of pyrasulfotole at 0.03 kg a.i./ha plus bromoxynil at 0.20 kg a.i./ha plus atrazine at 0.58 kg a.i./ha plus dicamba at 0.13 kg a.i./ha. Results from this research indicate that combinations of pyrasulfotole and bromoxynil can be effective in managing problematic weeds in Texas.